EFFECTIVE NEUROPSYCHOLOGICAL EVALUATION OF THE EXECUTIVE FUNCTION - Ingrid Buller P. (CAEN, 2010)
The following article comes in the development of a degree paper, and its original purpose pointed to assess the success of a neuropsychological rehabilitation program focused on the executive function. Nevertheless, it is possible to extend its usefulness as a complete and efficient instrument that allows an exhaustive diagnosis of the executive functioning to lead its accurate rehabilitation. The main importance of its consideration deals with the limitations observed in the context of the Chilean tertiary public attention, in terms of the lack of resources and benefits related to neuropsychological rehabilitation, and because of the need of a treatment focused on that very function that will secure better cognitive recovering for brain damaged patients served by such institutions.